From Fossil Fuels to Renewables: The Role of Electricity Storage - Itziar Lazkano; Linda Nøstbakken; Martino Pelli (Center for Economic Studies and ifo Institute (CESifo), 2016)
We analyze the role of electricity storage for technological innovations in electricity generation. We propose a directed technological change model of the electricity sector, where innovative firms develop better electricity storage solutions, which affect not only the relative competitiveness between renewable and nonrenewable electricity sources but also the ease with which they can be substituted. Using a global firm-level data set of electricity patents from 1963 to 2011, we empirically analyze the determinants of innovation in electricity generation, and the role of storage in directing innovation. Our results show that electricity storage increases innovation not only in renewables but also in conventional technologies. This implies that efforts to increase innovation in storage can benefit conventional, fossil fuel-fired electricity plants as well as increasing the use of renewable electricity.
Keywords: O30; O40; O50; Q20; Q30; Q40; Q50; 330; innovation; directed technical change; electricity storage; electricity markets; power generation